KARAKTERISTIK MORFOLOGI KELAPA SAWIT (Elaeis guineensis Jacq.) VARIETAS DyxP DUMPY DENGAN PEMBERIAN ASAM HUMAT PADA MEDIA TANAH SALIN DI MAIN NURSERY - Eka Bobby Febrianto; Hari Gunawan; Nona Valentine Sirait (Universitas Asahan, 2019)
Oil palm (Elaeis guineensis Jacq.) Is a plant species that has good adaptability in various environments. As a well-adapted plant, palm oil is very tolerant of mismatches in its handling and its normal growth can recover quickly from stress due to planting movements, drought, fires and other disruptions. The saline soil is an unsuitable type of soil for the growth of oil palm crops. Utilization of humic acid as a mixed organic material for saline soil, humic acid in the soil can act as a source of nutrients, maintaining soil moisture, as a buffer by chlorizing the elements causing salinity to increase the availability of nutrients. The study was conducted in the nursery area. The study period was 5 months, from January to June 2017. This study used Factorial 2 with 3x replication, the number of polybags per treatment was 3. The parameters test were arranged on the real variance checklist, followed by continued analysis with Duncan Multiple Range Test (DMRT ) with a rate of 5%. The results showed that humic acid treatment on saline soil medium with DHL level ≥4 mmhos / cm can increase plant height growth, leaf area index, root volume, root dry weight and dry weight of crown.